Lithium ion adsorbent as well as preparation method and application thereof

By using acid- and alkali-resistant polymers to coat lithium-ion sieves and controlling the formation of channels and micropores, the problems of high pressure drop and loss in industrial applications of lithium-ion sieves are solved, achieving a highly efficient lithium-ion adsorption and desorption process, which is suitable for large-scale industrial production.

CN119258998APending Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310835662.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing lithium-ion sieves are in powder form, which leads to large pressure drop, poor fluid flow, poor mass transfer, and easy loss in industrial applications, making it difficult to achieve large-scale industrial application.

Method used

Acid- and alkali-resistant polymers are used as coating materials. The formation of channels and micropores during the sphere formation process is controlled by pore-forming agents and foaming agents to prepare solid spheres. A coating mesh is formed on the surface of the spheres to improve mechanical strength and reduce lithium ion loss.

Benefits of technology

It improves the mass transfer efficiency and mechanical strength of lithium-ion adsorbents, reduces the loss of lithium-ion sieves, is suitable for large-scale industrial production, and reduces operating pressure and pressure drop.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258998A_ABST
    Figure CN119258998A_ABST
Patent Text Reader

Abstract

The invention relates to the field of lithium ion adsorbents, and discloses a lithium ion adsorbent and a preparation method and application thereof.The preparation method comprises the steps that 1, a first polymer, a first pore-foaming agent and a first solvent are subjected to first mixing, and a first ball casting solution is obtained; performing second mixing on a second polymer, a second pore-foaming agent and a second solvent to obtain a second ball casting solution; (2) mixing a lithium ion sieve precursor, a foaming agent and the first ball casting solution to obtain a solid-liquid mixture; (3) solidifying the solid-liquid mixture through dropping balls to obtain solid small balls; (4) the solid small balls make contact with a second ball casting solution and are solidified; the method further comprises the following steps: pickling a lithium ion sieve precursor and / or a product obtained in the step (4); the mass ratio of the first polymer to the first pore-foaming agent to the foaming agent is 1: (0.05-0.5): (0.05-0.5). The adsorbent prepared by the method is high in adsorption capacity, good in adsorption stability and easy to separate from a solution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion adsorbents, and in particular to a lithium ion adsorbent and a preparation method and application thereof. Background Art

[0002] With the rapid development of new energy vehicles, the sales volume of new energy vehicles has increased year by year; energy storage facilities also have great market prospects in the future, so the market has a huge demand for lithium resources.

[0003] In the existing technology, the precipitation method is suitable for lithium extraction from salt lake resources with relatively high lithium content; the extraction method has high selectivity for lithium, but the extractant is easy to deteriorate and contains phosphorus elements that affect the environment; the membrane separation method is relatively energy-saving, but the membrane cost is high, the membrane is prone to contamination, and it is not suitable for salt lake resources with low lithium content. The ion sieve adsorption method has good selectivity for lithium ions because the lithium ion sieve has a memory effect and an ion sieve effect on lithium ions. It is also suitable for lithium extraction from salt lakes with low lithium content and is a very promising lithium extraction method.

[0004] However, since the lithium ion sieve is in powder form, a large pressure drop will be generated in actual industrial production, which is not conducive to fluid flow, mass transfer between raw materials and the ion sieve, and will also cause powder loss, limiting the industrial application of the ion sieve. Summary of the invention

[0005] The purpose of the present invention is to overcome the problems of slow adsorption rate, poor stability and easy loss of ion sieve in the prior art ion sieve adsorbent, and to provide a lithium ion adsorbent and a preparation method and application thereof. The lithium ion adsorbent prepared by the preparation method has high adsorption capacity, is not easy to lose the ion sieve, has good adsorption stability, and is easy to separate from the solution.

[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a lithium ion adsorbent, comprising the following steps:

[0007] (1) performing a first mixing of a first polymer, a first porogen and a first solvent to obtain a first ball casting solution; performing a second mixing of a second polymer, a second porogen and a second solvent to obtain a second ball casting solution;

[0008] (2) mixing a lithium ion sieve precursor, a foaming agent and the first ball casting liquid to obtain a solid-liquid mixture;

[0009] (3) solidifying the solid-liquid mixture by dropping balls to obtain solid balls;

[0010] (4) contacting the solid ball with a second ball casting liquid to solidify;

[0011] Wherein, the method further comprises: acid washing the lithium ion sieve precursor and / or the product obtained in step (4);

[0012] Wherein, the mass ratio of the first polymer, the first porogen and the foaming agent is 1:(0.05-0.5):(0.05-0.5).

[0013] The second aspect of the present invention provides a lithium ion adsorbent prepared by the above preparation method.

[0014] The third aspect of the present invention provides use of the lithium ion adsorbent described in the second aspect in lithium ion extraction.

[0015] The preparation method of the lithium ion adsorbent provided by the present invention is simple, and uses an acid-resistant and alkali-resistant polymer as a coating material. The formation of pores and micropores in the balling process is regulated by a porogen and a foaming agent, so that the mass transfer effect of the lithium ion adsorbent in the adsorption and desorption process can be improved. The solid ball obtained by solidifying the drop ball is contacted with the second casting ball liquid, and a coating net can be formed on the surface of the ball, which further improves the mechanical strength of the adsorbent, reduces the loss of the lithium ion sieve, and helps to increase the service life of the adsorbent. No oil is needed in the ball forming process, and no calcination is needed for the later shaping. Therefore, the preparation method is suitable for large-scale industrial production, energy-saving and low-consumption, and is an economical and efficient lithium adsorbent preparation method.

[0016] The lithium ion adsorbent provided by the present invention is suitable for industrial lithium ion extraction. When applied to a lithium extraction adsorption tower, a lithium extraction adsorption column, and a lithium extraction fixed bed, the operating pressure is small, the pressure drop is small, and the loss of the ion screen can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is an appearance diagram of the lithium ion adsorbent prepared in Example 1;

[0018] Figure 2 is a cross-sectional SEM image of the lithium ion adsorbent prepared in Example 1 (magnification 130);

[0019] Figure 3 is a cross-sectional SEM image of the lithium ion adsorbent prepared in Example 1 (magnification 1.2k);

[0020] Figure 4 is a surface SEM image of the lithium ion adsorbent prepared in Example 1 (magnification 20k);

[0021] Figure 5 This is a cross-sectional SEM image of the lithium ion adsorbent prepared in Comparative Example 2 (magnification 600). DETAILED DESCRIPTION

[0022] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0023] The first aspect of the present invention provides a method for preparing a lithium ion adsorbent, comprising the following steps:

[0024] (1) performing a first mixing of a first polymer, a first porogen and a first solvent to obtain a first ball casting solution; performing a second mixing of a second polymer, a second porogen and a second solvent to obtain a second ball casting solution;

[0025] (2) mixing a lithium ion sieve precursor, a foaming agent and the first ball casting liquid to obtain a solid-liquid mixture;

[0026] (3) solidifying the solid-liquid mixture by dropping balls to obtain solid balls;

[0027] (4) contacting the solid ball with a second ball casting liquid to solidify;

[0028] Wherein, the method further comprises: acid washing the lithium ion sieve precursor and / or the product obtained in step (4);

[0029] Wherein, the mass ratio of the first polymer, the first porogen and the foaming agent is 1:(0.05-0.5):(0.05-0.5).

[0030] In the prior art, the conventional lithium ion sieve is in powder form. When used in lithium extraction adsorption towers, lithium extraction adsorption columns or lithium extraction fixed beds in industry, a large pressure drop will be generated, which is not conducive to fluid flow, and is not conducive to mass transfer between raw materials and ion sieves, and the powder will be lost. In addition, after adsorbing lithium ions, the ion sieve needs to be desorbed under acidic conditions, and ordinary molding materials such as aluminum oxide are not suitable for long-term use in such an environment.

[0031] The preparation method of the lithium ion adsorbent provided by the present invention is simple, and uses an acid-resistant and alkali-resistant polymer as a coating material. The formation of pores and micropores in the ball-forming process is regulated by a porogen and a foaming agent, so that the mass transfer effect of the lithium ion adsorbent in the adsorption and desorption process can be improved. The solid ball obtained by solidifying the drop ball is contacted with the second casting ball liquid, and a coating net can be formed on the surface of the ball, which further improves the mechanical strength of the adsorbent, reduces the loss of the lithium ion sieve, and helps to increase the service life of the adsorbent. No oil is needed in the ball forming process, and no calcination is needed in the later stage of finalization, which is suitable for large-scale industrial production.

[0032] It should be noted that the first mixing and the second mixing in the present invention do not refer to the order of operations, but are only used to distinguish different operations. The present invention has no particular limitation on the order of the steps, as long as the operations can be performed according to the direction of the materials.

[0033] According to the present invention, the mixture of the lithium ion sieve or the lithium ion sieve precursor and the first casting liquid is first drop-cured and then contacted with the second casting liquid to form a coating layer on the surface of the solid ball, thereby further improving the mechanical strength of the adsorbent, reducing the loss of the lithium ion sieve, and helping to increase the service life of the adsorbent. Preferably, the mass ratio of the lithium ion sieve or the lithium ion sieve precursor to the first casting liquid is 1:1-8, preferably 1:3-5, for example, it can be 1:3, 1:3.5, 1:4, 1:4.5, 1:5 and other typical but non-limiting ratios or a range between the two. Under the above-mentioned preferred dosage conditions, it can not only reduce the loss of the lithium ion sieve, but also enable sufficient contact between the lithium ion sieve and the liquid during the adsorption process, which is beneficial to improving the adsorption performance.

[0034] According to some preferred embodiments of the present invention, the mass ratio of the first polymer, the first porogen and the foaming agent is 1: (0.1-0.3): (0.1-0.4). Under the synergistic effect of the first polymer, the porogen and the foaming agent in the present invention, the formation of pores and micropores in the internal structure of the spheres during the spheroidization process can be better regulated. The porogen mainly regulates the nano-level pores and pore sizes in the microstructure, and the foaming agent mainly regulates the micron-level pores and pore sizes in the macrostructure of the ion sieve spheres. The combined effect of the two can help increase the contact area between the ion sieve sphere adsorbent and the solution, and help improve the mass transfer effect during the adsorption and desorption process.

[0035] In the present invention, preferably, based on the total amount of the first casting liquid, the content of the first polymer is 8-20wt%, preferably 15-20wt%, the content of the first porogen is 1-5wt%, preferably 1.5-4.5wt%, and the content of the first solvent is 75-91wt%, preferably 75.5-83.5wt%.

[0036] In the present invention, the compositions of the first ball casting liquid and the second ball casting liquid may be the same or different. Preferably, based on the total amount of the second ball casting liquid, the content of the second polymer is 8-20wt%, preferably 15-20wt%, the content of the second porogen is 1-5wt%, preferably 1.5-4.5wt%, and the content of the second solvent is 75-91wt%, preferably 75.5-83.5wt%.

[0037] According to the present invention, the acid- and alkali-resistant polymer refers to a polymer that has acid- and alkali-resistant properties, good chemical stability, and can stably exist in an acid- and alkali environment. Preferably, the first polymer and the second polymer are each independently selected from at least one of polyvinyl chloride (PVC, weight average molecular weight is preferably 100,000-400,000 g / mol), polysulfone (PSF, weight average molecular weight is preferably 100,000-400,000 g / mol), polyethersulfone (PES, weight average molecular weight is preferably 100,000-400,000 g / mol) and polyvinylidene fluoride (PVDF, weight average molecular weight is preferably 100,000-400,000 g / mol), and further preferably polyvinylidene fluoride.

[0038] In the present invention, the first solvent and the second solvent have a wide range of choices and can be selected from any solvent that has a solvent effect on the first polymer and the second polymer. Preferably, the first solvent and / or the second solvent are each independently selected from at least one of dimethylacetamide (DMAC), N,N-dimethylformamide (DMF) and N-methylpyrrolidone (NMP), and dimethylacetamide is more preferably selected.

[0039] In the present invention, the first porogen or the second porogen has a wide selection range and can be selected from conventional porogens in the art as long as they are soluble in the first solvent or the second solvent and the non-solvent. Preferably, the first porogen and the second porogen are each independently selected from at least one of polyvinyl pyrrolidone (PVP, preferably with a weight average molecular weight of 30,000-50,000 g / mol), polyethylene glycol (preferably with a weight average molecular weight of 10,000-20,000 g / mol) and Tween-80 (preferably with a weight average molecular weight of 500-700 g / mol), and more preferably polyvinyl pyrrolidone.

[0040] In the present invention, the foaming agent is used to regulate the micron-level pores in the macrostructure of the ion sieve beads, and can be selected from substances commonly used in the art that can generate gas when encountering acid; preferably, the foaming agent is selected from carbonates and / or bicarbonates, preferably at least one of sodium carbonate, potassium carbonate, calcium carbonate, magnesium carbonate, sodium bicarbonate, potassium bicarbonate, calcium bicarbonate and magnesium bicarbonate.

[0041] In the present invention, there is no particular limitation on the order of the first mixing or the second mixing. For example, the first mixing may be adding the first polymer and the first porogen together into the first solvent for dissolution to obtain the first ball casting solution; or the first polymer may be first mixed with the organic solvent, and then the first porogen is added for mixing to obtain the first ball casting solution. In order to improve the uniformity of mixing of the components, preferably, the first mixing includes first mixing the first polymer with the organic solvent, and then adding the first porogen for mixing to obtain the first ball casting solution.

[0042] The operation mode of the second mixing may be the same as the operation mode of the first mixing, which will not be described in detail here.

[0043] In the present invention, preferably, the conditions of the first mixing and / or the second mixing each independently include: a mixing temperature of 50-90° C., preferably 60-70° C., and a mixing time of 6-36 h, preferably 8-12 h.

[0044] Preferably, the first mixing and / or the second mixing are each independently performed under stirring conditions, and the stirring rate is 200-1000 rpm.

[0045] In the present invention, in order to prevent bubbles in the ball casting liquid from affecting the uniformity of subsequent mixing, preferably, the first mixing and the second mixing further include a standing process, and there is no special requirement for the standing time, as long as there are no bubbles in the first ball casting liquid and the second ball casting liquid.

[0046] In the present invention, in order to fully and evenly mix the ion sieve and the first ball casting liquid, preferably, the mixing in step (2) is carried out under stirring and / or ultrasonic conditions.

[0047] In the present invention, preferably, the drop-ball solidification is carried out by a non-solvent induced phase inversion method.

[0048] Preferably, the drop-ball solidification in step (3) comprises: dropping the solid-liquid mixture into a non-solvent through a dropper or a syringe, solidifying, washing, and drying to obtain solid balls.

[0049] In the present invention, the non-solvent refers to a solvent that has no dissolving effect on the first polymer and / or the second polymer. Preferably, the non-solvent is selected from alcohol and / or water; the alcohol is preferably selected from ethanol and / or propylene glycol.

[0050] In the present invention, there is no special limitation on the amount of the non-solvent. In order to fully realize the phase inversion effect and obtain better sphericity of the ion sieve beads, preferably, the depth of the non-solvent is 50-100 cm.

[0051] In the present invention, preferably, the outlet diameter of the dropper or injection is 0.4-3 mm. The needle diameter of the syringe is the outlet diameter of the syringe. The above preferred embodiment is helpful to control the particle size of the lithium ion adsorbent within the range of 1.5-4 mm, and the particle size is uniform.

[0052] In the present invention, preferably, the curing temperature is 25-40°C, preferably 30-35°C; the curing time is 2-24h, preferably 6-10h.

[0053] In the present invention, the washing and drying can be carried out using conventional operating methods and conditions in the art. Preferably, the drying temperature is 40-80° C. and the drying time is 2-6 hours.

[0054] According to some preferred embodiments of the present invention, the contacting in step (4) comprises: immersing the solid ball in a second casting liquid. The coating thickness is adjusted by controlling the contact time, preferably, the contact time is 0.1-0.2h, preferably 0.1-0.15h.

[0055] In the present invention, the solidification in step (4) includes: immersing the solid beads after contact in a non-solvent, and then washing and drying. The selection and dosage of the non-solvent, and the specific operations of washing and drying are the same as those in the above step (3), and will not be repeated here.

[0056] According to the present invention, the lithium ion sieve is an ion sieve that has an adsorption effect on lithium ions, and can be a mixture of one or more ion sieves that have an adsorption effect on lithium ions. The lithium ion sieve refers to a lithium ion sieve precursor that is acid-washed, and lithium ions on the crystal structure of the lithium ion sieve precursor are eluted to form adsorption sites with memory effect and ion sieve effect on lithium ions. After the lithium ion sieve precursor is acid-washed, a lithium ion sieve is obtained, such as after the lithium ion sieve precursor Li2TiO3 is acid-washed, a lithium ion sieve H2TiO3 is obtained.

[0057] According to some preferred embodiments of the present invention, the lithium ion sieve precursor is selected from LiMn2O4, Li 1.33 Mn 1.67 O4, Li2Mn3O7, Li4Mn5O 12 , Li 1.6 Mn 1.6 O4, Li2TiO3 and Li4Ti5O 12 At least one of the following, preferably Li2TiO3 and / or Li4Ti5O 12 .

[0058] In the present invention, there is no particular limitation on the source of the lithium ion sieve precursor, which can be purchased from a commercial source or prepared using a conventional preparation method in the art.

[0059] Li2TiO3 and / or Li4Ti5O 12 For example, the lithium ion sieve precursor can be prepared by the following preparation method, including: mixing a lithium source and a titanium source, and calcining to obtain a lithium ion sieve precursor.

[0060] The lithium source and titanium source can be conventional metal salts, oxides or hydroxides in the art. Preferably, the lithium source can be lithium carbonate and / or lithium acetate, and the titanium source can be titanium dioxide and / or titanium hydroxide. In order to increase the hydrophilicity of the ion sieve beads, preferably, the titanium source is titanium dioxide, which is beneficial to improve the hydrophilicity of the ion sieve beads, so that the aqueous solution can better wet the surface and internal pores of the ion sieve beads, thereby increasing the mass transfer effect.

[0061] Preferably, the lithium source and the titanium source are used in such an amount that the molar ratio of lithium to titanium is 1-2:1.

[0062] Preferably, the calcination conditions include: a calcination temperature of 500-850° C. and a calcination time of 6-10 h.

[0063] According to the present invention, the method further comprises: acid washing the lithium ion sieve precursor and / or the product obtained in step (4). The acid washing is used to elute the lithium ions on the crystal structure of the lithium ion sieve precursor in the lithium ion sieve precursor and / or the product obtained in step (4), forming adsorption sites having a memory effect and an ion sieve effect on lithium ions. Preferably, the acid washing comprises: contacting the lithium ion sieve precursor or the product obtained in step (4) with an eluent.

[0064] The present invention has a wide range of eluents, and any eluent conventionally used in the art for eluting lithium ion sieve precursors to obtain lithium ion sieves can be applied to the present invention. Preferably, the eluent is provided by an aqueous acid solution, preferably at least one selected from aqueous solutions of hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, oxalic acid, fruit acid, formic acid, acetic acid and citric acid, more preferably an aqueous solution of hydrochloric acid.

[0065] Preferably, the concentration of the aqueous solution of the acid is 0.05-3 mol / L, preferably 0.1-1 mol / L.

[0066] Preferably, the mass ratio of the lithium ion sieve precursor or the product obtained in step (4) to the eluent is 1:(20-100). Preferably, the mass ratio of the lithium ion sieve precursor or the product obtained in step (4) to the eluent is 1:(90-100).

[0067] It is understandable that in the present invention, the lithium ion sieve precursor can be directly subjected to steps (2)-(4) and then acid-washed, or the lithium ion sieve precursor can be acid-washed to obtain the lithium ion sieve and then steps (2)-(4) can be performed.

[0068] Preferably, the lithium ion sieve precursor can be directly subjected to steps (2)-(4) and then pickled. According to the present invention, after the lithium ion sieve precursor pellets are prepared, pickling is performed. Since the casting liquid contains porogens and foaming agents, the external surface and the interior of the lithium ion sieve precursor pellets are porous structures, and the acid solution can also normally enter the interior of the lithium ion sieve precursor pellets, pickling the lithium ion sieve precursor on the pellet skeleton, eluting the lithium ions on the lithium ion sieve precursor, and forming adsorption sites with memory effect and ion sieve effect on lithium ions. In the prior art, since the internal pore structure of the sphere is poor after balling, it is difficult to elute the lithium ion sieve precursor on the internal skeleton, so it is usually necessary to elute it before molding, but since the lithium ion sieve precursor is in powder form, washing, filtering and drying are difficult, which will undoubtedly greatly increase the preparation process and increase energy consumption.

[0069] According to some specific embodiments of the present invention, the method for preparing the lithium ion adsorbent comprises:

[0070] (b1) mixing a first polymer, a first porogen and a first solvent to obtain a first ball casting solution; and mixing a second polymer, a second porogen and a second solvent to obtain a second ball casting solution;

[0071] (b2) mixing the lithium ion sieve precursor, the foaming agent and the first ball casting liquid to obtain a solid-liquid mixture;

[0072] (b3) solidifying the solid-liquid mixture by dropping balls to obtain solid balls;

[0073] (b4) contacting the solid ball with a second ball casting liquid to solidify;

[0074] (b5) washing the product obtained in step (b4) with acid.

[0075] The adoption of the above-mentioned preferred implementation mode is beneficial to reducing the preparation steps, reducing the filtering time, washing times, and drying times, which is beneficial to shortening the preparation process, reducing the generation of organic wastewater and acid solution, saving washing water, and saving energy consumption.

[0076] The second aspect of the present invention provides a lithium ion adsorbent prepared by the above preparation method.

[0077] Preferably, the diameter of the lithium ion adsorbent is 1.5-4 mm.

[0078] Preferably, the pore size on the surface of the lithium ion adsorbent is 50nm-200nm.

[0079] The third aspect of the present invention provides use of the lithium ion adsorbent described in the second aspect in lithium ion extraction.

[0080] The lithium ion extraction is preferably carried out in a lithium extraction adsorption tower, a lithium extraction adsorption column, or a lithium extraction fixed bed, which is beneficial to reducing the pressure drop of the liquid passing through the lithium ion adsorbent and is beneficial to the industrial application of the ion sieve adsorption method.

[0081] The present invention will be described in detail below through examples.

[0082] In the following examples, the raw materials used were all purchased from commercial sources.

[0083] The adsorption amount of ions was measured by ICP analysis method.

[0084] The following preparation example is used to illustrate the preparation of ion sieves.

[0085] Preparation Example 1

[0086] S1. Lithium carbonate and titanium dioxide are weighed according to the molar ratio of lithium to titanium of 2:1, the lithium carbonate and titanium dioxide are evenly mixed, and reacted at 850°C for 10 hours to obtain a lithium ion sieve precursor Li2TiO3;

[0087] S2. The ion sieve precursor is impregnated with 0.8 mol / L dilute hydrochloric acid for 10 hours. The mass ratio of the ion sieve precursor to the dilute hydrochloric acid is 1:100. The lithium ions on the crystal structure of the ion sieve precursor are eluted. The acid washing time is 6 hours. After that, the remaining acid on the ion sieve adsorbent is washed away with deionized water, and then dried to obtain a lithium ion sieve powder with a composition of H2TiO3. After testing, the saturated adsorption capacity of this powder ion sieve for lithium ions is 23 mg / g.

[0088] The following examples are used to illustrate the preparation of lithium ion adsorbents.

[0089] Example 1

[0090] (1) 3.0 g of polyvinylidene fluoride (weight average molecular weight of 300,000 g / mol) and 0.82 g of polyvinyl pyrrolidone (weight average molecular weight of 30,000 g / mol) were added to 15.1 g of dimethylacetamide, and the mixture was stirred evenly. The temperature was controlled at 70° C. and the mixture was stirred at 300 rpm for 7 h. The mixture was allowed to stand to remove bubbles. After the bubbles were removed, a first ball casting liquid was obtained. A second ball casting liquid was prepared according to the same operation. The second ball casting liquid had the same composition as the first ball casting liquid.

[0091] (2) Take 13.1 g of the first casting liquid, 4.1 g of the lithium ion sieve H2TiO3 prepared in Preparation Example 1,

[0092] 800.0 mg sodium carbonate, mechanically stirred and ultrasonically treated until mixed uniformly to obtain a solid-liquid mixture;

[0093] (3) Add the solid-liquid mixture to a syringe pump, squeeze it out through a 0.8 mm needle, and drop it into 30°C water with a water depth of 50 cm. After 6 hours, remove it from the water, wash it, and dry it at 45°C for 3 hours to obtain solid pellets.

[0094] (4) The solid balls were added to the second casting liquid and soaked for 6 minutes, then taken out, the liquid on the surface of the solid balls was shaken off, and then sprinkled into water. After soaking for 2 hours, the solid balls were taken out, washed, and dried at 45°C for 3 hours to obtain lithium ion adsorbent S1 with an average particle size of 2 mm. The appearance of S1 is as follows: Figure 1 shown.

[0095] The cross-sectional SEM of the lithium ion adsorbent is shown in Figure 2. Figure 2 and Figure 3 As shown in the figure, it can be seen that the inside of the ball has formed a structural channel from the inside to the outside and a hole with a size of about 1 micron. Figure 4 As shown, the surface pore diameter is between 50nm and 200nm, and it can be seen that a mesh coating layer is formed on the surface of the sphere.

[0096] Example 2

[0097] (1) 14.4 g of polyvinylidene fluoride (weight average molecular weight of 300,000 g / mol) and 1.54 g of polyvinyl pyrrolidone (weight average molecular weight of 30,000 g / mol) were added to 64 g of dimethylacetamide, and the mixture was stirred evenly. The temperature was controlled at 70° C. and the mixture was stirred at 300 rpm for 7 h. The mixture was allowed to stand to remove bubbles. After the bubbles were removed, a first ball casting liquid was obtained. A second ball casting liquid was prepared according to the same operation. The second ball casting liquid had the same composition as the first ball casting liquid.

[0098] (2) 75 g of the first casting liquid prepared as above, 15.6 g of the lithium ion sieve precursor Li2TiO3 prepared in Preparation Example 1, and 1500 mg of sodium bicarbonate were mixed, mechanically stirred and ultrasonically treated until the mixture was uniform, to obtain a solid-liquid mixture;

[0099] (3) Add the solid-liquid mixture to a syringe pump, squeeze it out through a 0.8 mm needle, and drop it into 35° C. water with a depth of 80 cm. After 2 hours, remove it from the water, wash it, and dry it at 50° C. for 3 hours to obtain solid pellets.

[0100] (4) Add the solid balls to the second ball casting liquid and soak for 6 minutes, remove them, shake off the liquid on the surface of the solid balls, and then sprinkle them into water. After soaking for 2 hours, remove them, wash them, and dry them at 45°C for 3 hours.

[0101] (5) The product obtained in step (4) was added to dilute hydrochloric acid at 45°C and a concentration of 0.6 mol / L for acid immersion for 6 hours, wherein the mass ratio of the product obtained in step (4) to the dilute hydrochloric acid was 1:100; and then washed and dried to obtain a lithium ion adsorbent S2 having an average particle size of 2 mm.

[0102] Example 3

[0103] (1) adding 3 g of polyvinylidene fluoride (weight average molecular weight of 300000 g / mol) and 0.82 g of polyvinyl pyrrolidone (weight average molecular weight of 30000 g / mol) to 15.1 g of N,N-dimethylformamide, stirring evenly, controlling the temperature at 70° C., stirring at 300 rpm for 7 h, standing to remove bubbles, and obtaining a first ball casting liquid after no bubbles are present; preparing a second ball casting liquid according to the same operation, and the second ball casting liquid has the same composition as the first ball casting liquid;

[0104] (2) 13.1 g of the first casting liquid prepared as above, 4.1 g of the lithium ion sieve precursor Li2TiO3 prepared in Preparation Example 1, and 800 mg of calcium carbonate were mechanically stirred and ultrasonically treated until the mixture was uniformly mixed to obtain a solid-liquid mixture;

[0105] (3) Add the solid-liquid mixture to a syringe pump, squeeze it out through a 0.8 mm needle, and drop it into 30° C. water with a depth of 50 cm. After 2 hours, remove it from the water, wash it, and dry it at 50° C. for 3 hours to obtain solid pellets.

[0106] (4) Add the solid balls to the second ball casting liquid and soak for 6 minutes, remove them, shake off the liquid on the surface of the solid balls, and then sprinkle them into water. After soaking for 2 hours, remove them, wash them, and dry them at 45°C for 3 hours.

[0107] (5) The product obtained in step (4) was added to 40° C., 0.5 mol / L dilute hydrochloric acid for acid immersion for 5 hours, wherein the mass ratio of the product obtained in step (4) to the dilute hydrochloric acid was 1:95; and then washed and dried to obtain a lithium ion adsorbent S3 having an average particle size of 2 mm.

[0108] Example 4

[0109] (1) adding 15 g of polyvinylidene fluoride (weight average molecular weight of 300,000 g / mol) and 0.75 g of polyvinyl pyrrolidone (weight average molecular weight of 30,000 g / mol) to 71 g of dimethylacetamide, stirring evenly, controlling the temperature at 70° C., stirring at 300 rpm for 7 h, standing to remove bubbles, and obtaining a first ball casting liquid after no bubbles are present; preparing a second ball casting liquid according to the same operation, the second ball casting liquid having the same composition as the first ball casting liquid;

[0110] (2) 75 g of the first casting liquid prepared as above, 15.6 g of the lithium ion sieve precursor Li2TiO3 prepared in Preparation Example 1, and 700 mg of sodium bicarbonate were mixed, mechanically stirred and ultrasonically treated until the mixture was uniform, to obtain a solid-liquid mixture;

[0111] (3) Add the solid-liquid mixture to a syringe pump, squeeze it out through a 0.8 mm needle, and drop it into 35° C. water with a depth of 80 cm. After 2 hours, remove it from the water, wash it, and dry it at 50° C. for 3 hours to obtain solid pellets.

[0112] (4) Add the solid balls to the second ball casting liquid and soak for 6 minutes, remove them, shake off the liquid on the surface of the solid balls, and then sprinkle them into water. After soaking for 2 hours, remove them, wash them, and dry them at 45°C for 3 hours.

[0113] (5) The product obtained in step (4) was added to dilute hydrochloric acid at 45°C and a concentration of 0.6 mol / L for acid immersion for 6 hours, wherein the mass ratio of the product obtained in step (4) to the dilute hydrochloric acid was 1:100; and then washed and dried to obtain a lithium ion adsorbent S2 having an average particle size of 2 mm.

[0114] The prepared lithium ion adsorbent is recorded as S4.

[0115] Example 5

[0116] According to the method of Example 2, the difference is that the first ball casting liquid and the lithium ion sieve precursor Li2TiO3 are mixed in a mass ratio of 10:1, and 50g of the first ball casting liquid, 5g of the lithium ion sieve precursor Li2TiO3,

[0117] The mixture was mixed with 500 mg of sodium bicarbonate, mechanically stirred and ultrasonically treated until the mixture was uniformly mixed to obtain a solid-liquid mixture.

[0118] The prepared lithium ion adsorbent is recorded as S5.

[0119] Comparative Example 1

[0120] (1) Add 15 g of polyvinylidene fluoride (weight average molecular weight of 300,000 g / mol) to 64 g of dimethylacetamide, stir evenly, control the temperature at 80° C., stir at 300 rpm for 7 h, let stand to remove bubbles, and obtain the first ball casting liquid after there are no bubbles;

[0121] (2) 60 g of the first casting liquid prepared as above and 15 g of the lithium ion sieve precursor Li2TiO3 prepared in Preparation Example 1 were mechanically stirred and ultrasonically treated until they were uniformly mixed to obtain a solid-liquid mixture;

[0122] (3) Add the solid-liquid mixture to a syringe pump, squeeze it out through a 0.8 mm needle, and drop it into 30° C. water with a depth of 80 cm. After 2 hours, remove it from the water, wash it, and dry it at 50° C. for 3 hours to obtain solid pellets.

[0123] (4) The product obtained in step (3) was added to dilute hydrochloric acid at 45°C and a concentration of 0.6 mol / L and impregnated for 6 hours. The mass ratio of the product obtained in step (4) to the dilute hydrochloric acid was 1:100, and then washed and dried to obtain a lithium ion adsorbent DS1 with an average particle size of 2 mm.

[0124] Comparative Example 2

[0125] (1) adding 12 g of polyvinylidene fluoride (weight average molecular weight of 300,000 g / mol) to 64 g of dimethylacetamide, stirring evenly, controlling the temperature at 80° C., stirring at 300 rpm for 7 h, standing to remove bubbles, and obtaining a first ball casting liquid after no bubbles are present; preparing a second ball casting liquid according to the same operation, and the second ball casting liquid has the same composition as the first ball casting liquid;

[0126] (2) 50 g of the first casting liquid prepared as above, 12 g of the lithium ion sieve precursor Li2TiO3 prepared in Preparation Example 1, and 2000 mg of sodium bicarbonate were ultrasonically treated until they were uniformly mixed to obtain a solid-liquid mixture;

[0127] (3) Add the solid-liquid mixture to a syringe pump, squeeze it out through a 0.8 mm needle, and drop it into 30° C. water with a depth of 80 cm. After 2 hours, remove it from the water, wash it, and dry it at 50° C. for 3 hours to obtain solid pellets.

[0128] (4) Add the solid balls to the second ball casting liquid and soak for 6 minutes, remove them, shake off the liquid on the surface of the solid balls, and then sprinkle them into water. After soaking for 2 hours, remove them, wash them, and dry them at 45°C for 3 hours.

[0129] (5) The product obtained in step (4) was added to 45°C, 0.6 mol / L dilute hydrochloric acid for acid immersion for 6 hours, the mass ratio of the product obtained in step (4) to the dilute hydrochloric acid being 1:100, and then washed and dried to obtain lithium ion adsorbent DS2. The cross-sectional morphology of DS2 is as follows: Figure 5 As shown, it can be seen that the cross-section of the prepared sphere has only grooves caused by bubbles, and the structure is relatively compact.

[0130] Performance Testing:

[0131] A test solution containing equal amounts of potassium ions, calcium ions, sodium ions, magnesium ions and lithium ions was prepared, and the ion content was 200 mg / L. 1 g of the lithium ion adsorbent prepared in the above embodiment and comparative example was added to 100 g of the test solution, and an absorption test was performed at 45° C. After 3 hours, the adsorbed solution was analyzed by ICP to obtain the first adsorption amount. The results are shown in Table 1.

[0132] Adsorption amount (mg / g) = (mass of Li ions in the original solution - mass of Li ions in the solution after adsorption) / mass of the ion sieve of the lithium ion sieve adsorption beads.

[0133] The adsorbed lithium ion adsorbent is subjected to acid washing and desorption, and the specific method includes: using dilute hydrochloric acid with a concentration of 1 mol / L for acid washing, the acid washing time is 2 hours, the acid washing temperature is 50°C, and the mass ratio of the lithium ion adsorbent to the dilute hydrochloric acid is 1:100.

[0134] The lithium ion adsorbents prepared in the above examples and comparative examples were subjected to adsorption-desorption cycle tests. After 5 cycles, the adsorbed solution was analyzed by ICP. The results are shown in Table 1.

[0135] Table 1

[0136] serial number First adsorption amount mg / g Adsorption capacity after 5 cycles mg / g S1 15.9 15.9 S2 15.2 15.2 S3 14.7 14.7 S4 7.1 7.1 S5 5.9 5.9 DS1 1.5 0.7 DS2 2.6 2.6

[0137] In the adsorption-desorption cycle test of the ion sieve adsorbent, an important factor affecting the cyclic adsorption amount is the dissolution rate of the ion sieve. With the acid washing and desorption, the ion sieve powder is lost, and the titanium ions in the ion sieve structure are also eluted, resulting in a decrease in the cyclic adsorption amount. Combined with the results in Table 1, it can be seen that the lithium ion adsorbent prepared by the preparation method provided in the embodiment of the present invention can maintain a considerable adsorption amount after 5 adsorption-desorption cycles, and no titanium ions are detected in the solution after desorption, which proves that the dissolution rate of the ion sieve is low and the service life of the adsorbent is long.

[0138] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a lithium ion adsorbent, characterized in that: The following steps are involved: (1) mixing a first polymer, a first porogen, and a first solvent to obtain a first ball casting liquid; performing a second mixing of a second polymer, a second porogen, and a second solvent to obtain a second ball casting liquid; (2) mixing a lithium ion sieve precursor, a foaming agent and the first ball casting liquid to obtain a solid-liquid mixture; (3) solidifying the solid-liquid mixture by dropping balls to obtain solid balls; (4) contacting the solid ball with a second ball casting liquid to solidify; Wherein, the method further comprises: acid washing the lithium ion sieve precursor and / or the product obtained in step (4); Wherein, the mass ratio of the first polymer, the first porogen and the foaming agent is 1:(0.05-0.5):(0.05-0.5).

2. The preparation method according to claim 1, wherein The mass ratio of the first polymer, the first porogen and the foaming agent is 1:(0.1-0.3):(0.1-0.4); Preferably, the mass ratio of the lithium ion sieve precursor to the first ball casting liquid is 1:1-8, preferably 1:3-5.

3. The preparation method according to claim 1 or 2, wherein Based on the total amount of the first ball casting liquid, the content of the first polymer is 8-20wt%, the content of the first porogen is 1-5wt%, and the content of the first solvent is 75-91wt%.

4. The preparation method according to claim 1 or 2, wherein: Based on the total amount of the second ball casting liquid, the content of the second polymer is 8-20wt%, the content of the second porogen is 1-5wt%, and the content of the second solvent is 75-91wt%; And / or, the conditions of the first mixing and / or the second mixing each independently include: a mixing temperature of 50-90° C., a mixing time of 6-36 h; Preferably, the first mixing and / or the second mixing are each independently performed under stirring conditions, and the stirring rate is 200-1000 rpm.

5. The preparation method according to any one of claims 1 to 4, wherein: The first polymer and the second polymer are each independently selected from at least one of polyvinyl chloride, polysulfone, polyethersulfone and polyvinylidene fluoride, preferably polyvinylidene fluoride; Preferably, the first solvent and the second solvent are each independently selected from at least one of dimethylacetamide, N,N-dimethylformamide and N-methylpyrrolidone, preferably dimethylacetamide; Preferably, the first porogen and the second porogen are each independently selected from at least one of polyvinyl pyrrolidone, polyethylene glycol and Tween-80, preferably polyvinyl pyrrolidone; Preferably, the foaming agent is selected from carbonates and / or bicarbonates, preferably at least one of sodium carbonate, potassium carbonate, calcium carbonate, magnesium carbonate, sodium bicarbonate, potassium bicarbonate, calcium bicarbonate and magnesium bicarbonate.

6. The preparation method according to any one of claims 1 to 5, wherein: The drop ball solidification in step (3) comprises: dropping the solid-liquid mixture into a non-solvent through a dropper or a syringe, solidifying, washing, and drying to obtain solid balls; Preferably, the outlet diameter of the dropper or injection is 0.4-3 mm; Preferably, the curing temperature is 25-40°C and the curing time is 2-24h; Preferably, the non-solvent is selected from alcohol and / or water; Preferably, the drying temperature is 40-80°C and the drying time is 2-6h; Preferably, in step (4), the contact time is 0.1-0.2 h, preferably 0.1-0.15 h.

7. The preparation method according to any one of claims 1 to 6, wherein: The lithium ion sieve precursor is selected from LiMn2O4, Li 1.33 Mn 1.67 O4, Li2Mn3O7, Li4Mn5O 12 , Li 1.6 Mn 1.6 O4, Li2TiO3 and Li4Ti5O 12 At least one of the following, preferably Li2TiO3 and / or Li4Ti5O 12 .

8. The preparation method according to any one of claims 1 to 7, wherein: The acid washing comprises: contacting the lithium ion sieve precursor or the product obtained in step (4) with an eluent; Preferably, the eluent is provided by an aqueous solution of an acid, preferably at least one selected from aqueous solutions of hydrochloric acid, sulfuric acid, phosphoric acid, nitric acid, oxalic acid, fruit acid, formic acid, acetic acid and citric acid, more preferably an aqueous solution of hydrochloric acid; Preferably, the concentration of the aqueous solution of the acid is 0.05-3 mol / L, preferably 0.1-1 mol / L; Preferably, the mass ratio of the lithium ion sieve precursor or the product obtained in step (4) to the eluent is 1:(20-100).

9. The lithium ion adsorbent prepared by the method for preparing the lithium ion adsorbent according to any one of claims 1 to 8.

10. Use of the lithium ion adsorbent according to claim 9 in lithium ion extraction.